Dairy Cow Reproduction Display (Friesian Holstein) at KPBS Pangalengan Bandung Regency - Sudrajat, Ajat; Khaerudin, Asep Rahmat; Christi, Raden Febrianto (Universitas Halu Oleo, 2022)
Research on the reproduction of Friesian Hostain cows at KPBS Pangalengan has been conducted. The purpose of this study is to find out, review and evaluate the reproduction of FH cows in KPBS Pangalengan Bandung Regency. The research method uses survey methods, data collection is done purposive sampling with the criteria of dairy cows that have lactation and have children at least twice and sampling on 47 respondents of cooperative members. The variables analyzed are the first age of estrus, the age of the childcracker, open days and service per conception. Data analysis is done descriptively. The results showed that the average age of the first age of FH cow estrus in KPBS Pangalengan was 14.29 months, the average first age of children was 27.08 months, the average days open (DO) 3.33 months and the average Service per conception (S /C) 1.69 times. It can be concluded that the display of reproduction of Friesian Hostain cows in KPBS Pangalengan is good enough. Keywords: Holstein Friesian Cow, reproduction, days open, Service per conception and KPBS Pangalengan